Aktivitas Bakterisida dan Fungisida Ekstrak Kasar Biji Kolowe - Helmi, Henny (ENVIAGRO, 2008)
Kolowe seed crude extract contain of saponin, triterpenoid, polyphenol and alealoid.  Kolowe seeds were extracted with methanol by maseration, metanol extract was partition with ethil acetat and n-buthanol.  The research to evaluate bactericide and fungicide activity of kolowe seeds crude extract has been done. The activities of bactericide and fungicide potential were tested by hole plate diffusion method. The result shows that the methanol extract may, inhibit the growth of Clavibacter michiganense and Ralstonia solanacearum with the average of inhibition area 11.53 mm and 10.6 mm respectively.  The result also exhibits that methanol extract could inhibit the growth of Alternaria porii with the average of inhibition area 10.4 mm while n-buthanol inhibit Colletotrichum gloesporioides with the average of inhibition area 10.2 mm. Key Words: extract, bactericide, fungicide, kolowe seed, methanol, n-buthanol, etil asetat